The high altitude medical studies in Japan - Nakashima, Michiro (Acta Andina, 2025)
Japanese high altitude medical study began at Manaslu Expedition in 1953, Since then, among many expeditions to Himalaya from Japan, 34 of them have repor ted medical research works. Eight reports were remarkable among these 34 expeditions, and especially two of them were distinguished. These two reports were Japanese Alpine Club Mt. Everest Expedition, 1970 (JMEE’70) and Kyoto University Medical Research Expedition to Xixabangma, 1990 (KUMREX’90). Abstract of some papers on KUMREX’90 are introduced here. The Japanese Society of Mountain Medicine(JSMM) was established in 1981, and the Japanese Journal of Mountain Medicine(JJMM), proceedings of the annual meeting of the Japanese Symposium on Mountain Medicine is being published every year. JJMM vol. 16, the latest issue, was published in Dec. 1996. Among many Japanese medical researcher-mountain climbers, Dr. Matsubayashi, Dr. Saito, Dr. Masuyama and Dr. Horii did remarkable works and some of their main works are introduced here. Since 1966, many cases of severe AMS(HAPE/HACE) have been reported in Japan though there are not many mountains higher than 3,000m. Dr. Kobayashi and his colleagues have reported researches on many HAPE cases and high susceptibility to high altitude of the cases. Besides expedition medicine, physiological research works on simulated altitude are also carring out at several universities. Dr. Asano of Tsukuba University is the leader of this field in Japan.